Dehydrogenative Lactonization of Diols in Aqueous Media Catalyzed by a Water‐Soluble Iridium Complex Bearing a Functional Bipyridine Ligand. Issue 1 (24th November 2013) - Fujita, Ken‐ichi; Ito, Wataru; Yamaguchi, Ryohei
Abstract A new catalytic system for the dehydrogenative lactonization of a variety of benzylic and aliphatic diols in aqueous media was developed. By using a water‐soluble, dicationic iridium catalyst bearing 6, 6′‐dihydroxy‐2, 2′‐bipyridine as a functional ligand, highly atom economical and environmentally benign synthesis of various lactones was achieved in good to excellent yields. Recovery and reuse of the catalyst were also accomplished by a simple phase separation and the recovered catalyst maintained its high activity at least until the fifth run.